COMMON FIXED POINT THEOREMS OF INTEGRAL TYPE IN MENGER PM SPACES - Altun, I.; Tanveer, M.; Imdad, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper, we propose integral type common fixed point theorems in Menger spaces satisfying common property (E.A). Our results generalize several previously known results in Menger as well as metric spaces. Some related results are also derived besides furnishing an illustrative example.